Angiogenic potential of dental stem cells seeded on human amniotic membrane as a scoffold for pulp tissue regeneration - Ahmad, Azlina (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2017)
Regenerative medicine, particularly in wound healing, is necessary for the mankind. Our study aim to investigate the angiogenic potential of a 3D model made up of Human Amniotic Membrane (HAM) scaffold; Human Exfoliated Deciduous Teeth (SHED) and Vascular Endothelial Growth Factor (VEGF). SHED grew on the stromal side of HAM had the ability to proliferate, migrate and differentiate. The SEM analysis revealed that SHED cultured on HAM with the addition of VEGF change its fibroblast-like shape into rounded-like shape. Besides, H&E analysis also showed the ability of SHED cell to form monolayer structure on stromal surfaces until day 14. However, on day 21 , cells started to infiltrate inside the HAM stromal layer. The infiltration could happen due to cell differentiation, where SHED might change its size, allowing cells to invade inside this fibrous structure. Gene analysis also revealed the potential of endothelial-like differentiation. Even though there was no expression of VEGFR2 and CD31 genes, protein analysis showed the expression of Cox-2. The Cox-2 expression is involved in the formation of the tubule. All the results proved that SHED has a potential to differentiate and involved in angiogenesis with the help of extracellular matrix components on HAM.